Update on Hereditary Kidney Stone Disease and Introduction of a New Clinical Patient Registry in Germany - Halbritter, Jan; Seidel, Anna; Müller, Luise; Schönauer, Ria; Hoppe, Bernd (Frontiers in Pediatrics, 2018)
Kidney stone disease is an increasingly prevalent condition with remarkable clinical heterogeneity, with regards to stone composition, age of manifestation, rate of recurrence, and impairment of kidney function. Calcium-based kidney stones account for the vast majority of cases but their etiology is poorly understood, notably their genetic drivers. As recent studies indicate, hereditary conditions are most likely underestimated in prevalence and new disease genes are constantly being identified. As a consequence, there is an urgent need of a more efficient documentation and collection of cases with underlying hereditary conditions, in order to better understand shared phenotypic presentation and common molecular mechanisms. By implementation of a centralized patient registry on hereditary kidney stone disease in Germany, we aim to help closing the vast knowledge gap on genetics of kidney stone disease. In this context, clinical registries are advantageous for several reasons: First, delineating better phenotype-genotype associations will allow more precise patient stratification in future clinical research studies. Second, identifying new disease genes and new mechanisms will further reduce the rate of unknown NL/NC-etiology; and third, deciphering new molecular targets will pave the way to develop drugs for recurrence prevention in severely affected families.